Optimising urban measurement networks for CO2 flux estimation: a high-resolution observing system simulation experiment using GRAMM/GRAL [data] - Vardag, Sanam Noreen; Maiwald, Robert (Universität, 2023)
CO2 concentration fields in Heidelberg were simulated using the model GRAMM v19.01/GRAL v19.01. GRAL uses the GRAMM wind fields as mesoscale input and refines the wind fields to a higher resolution taking into account the flow around buildings. The GRAL domain size is 12.3km x12.3km with 10m x 10m horizontal resolution and 2m vertical resolution. A Lagrangian particle simulation is performed to obtain the hourly steady state particle distribution from emissions, which is used to compute the concentration field. The model GRAMM and a link to its documentation can be found here: https://github.com/GralDispersionModel/GRAMM The model GRAL and a link to the documentation can be found here: https://github.com/GralDispersionModel/GRAL
Gesehen am 02.10.2023
Keywords: Forschungsdaten; Datenbank